2012
DOI: 10.2139/ssrn.1646471
|View full text |Cite
|
Sign up to set email alerts
|

The Costs of Shareholder Activism: Evidence from a Sequential Decision Model

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 39 publications
1
82
0
Order By: Relevance
“…The first looks at hedge fund activism and is borrowed from Gantchev (2013). Gantchev uses data from 13D filings, proxies, and SharkRepellent.net to track the evolution of activist campaigns instigated by a large set of activist hedge funds between 2000 and 2008.…”
Section: Columns 1 Through 3 Inmentioning
confidence: 99%
“…The first looks at hedge fund activism and is borrowed from Gantchev (2013). Gantchev uses data from 13D filings, proxies, and SharkRepellent.net to track the evolution of activist campaigns instigated by a large set of activist hedge funds between 2000 and 2008.…”
Section: Columns 1 Through 3 Inmentioning
confidence: 99%
“…Payout at these companies before intervention is lower than that of matched firms indicating a shareholder value creation. Gantchev (2013) modelled hedge fund activism as a sequential decision process consisting of demand negotiations, board representation and proxy contest and estimated the costs of each distinct stage. It was found that the estimated monitoring costs consume more than twothirds of gross activist returns implying that the net returns to activism are significantly lower than previously thought.…”
Section: Shareholder Activismmentioning
confidence: 99%
“…The dissatisfaction of some shareholders with the firm's performance or its management may lead them to consider active and aggressive means to safeguard their interests in the firm and they may become an activist. Activism is a costly affair (Gantchev 2013), and activists weigh their outcomes before committing their resources to a target firm. Unlike the popular image, the observation by some researchers shows that most activists use peaceful means like a dialogue with the board or management at the target firm rather than get confrontational with them.…”
Section: Investor Activismmentioning
confidence: 99%
“…While many have tried to imitate successful activist investors, the performance varies among the activists. Considering monitoring costs and the net returns to shareholder activism, Gantchev (2013) found that the mean net activist return is close to zero but the top quartile of activists earn higher returns on their activist holdings than on their non-activist investments.…”
Section: 186mentioning
confidence: 99%